In uence of threshing unit design of axial flow rice combine harvesters on harvesting losses when harvesting Thai Hommali Rice - Chuan-Udom, Somchai; Chinsuwan, Winit (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this research was to study the in uence of threshing unit design of axial ow rice combine harvesters on harvesting losses when harvesting Thai Hommali rice. The sample consisted of 17 machines in Tung Kula Ronghai area. The result of the research indicated that the number of tooth (NT) was the most in uenced on the loss and was equal 30.43%. The second and third in uence on the loss were the clearance between the lower concave and the tip of the tooth in horizontal (SC), and the clearance between the upper concave and tip of the tooth in vertical (UC) which were 28.20% and 27.31% respectively. The concave clearance (CC), the concave rod clearance (RC), the rotor diameter (RD), and the height of tooth (HT) were low in uenced on the loss which were equal 9.07%, 2.58%, 2.40%, and 1.07% respectively.